Implementation of the At-Taisir Concept in the National Sharia Council's Mudharabah Agreement Fatwa - Muhammad Ali Akbarsyah; Imron Rosyadi; Muthoifin (al-Afkar, Journal For Islamic Studies, 2024)
Since the development of the Islamic economy in the early 90s, Muslim communities have demanded a legal decision from experts regarding the system in the economy. One of the contracts that is being discussed is mudharabah. Because mudharabah is a way out of the usury system which makes the owners of large capital bigger and the poor poorer. This research uses literature. By digging up data from books, journals and other written references. So the results and conclusions are a review of the available books. As well as with descriptive analysis methods. Explain in description the problem of the concept of taisir in the MUI fatwa regarding the mudharabah contract. This research concludes that the mudharabah contract is legally permissible as long as it is permissible, it is a contract containing the rukhshah of a haram contract with a ribawi system. The DSN MUI fatwa has its own manhaj in accommodating various things in Indonesia. The results of the DSN MUI fatwa have the following technical implications: (1) mudharabah is a solution to a usurious interest system; (2) the size and size of financing from LKS to customers can be adjusted to existing data and documents; (3) as long as there are no eligible LKS, there are rukhsahs for the use of conventional bank services. So that economic growth with mudharabah includes comprehensive prosperity; receive blessings; and economic equality and empowerment of MSMEs.